STUDY ON MECHANICAL CHARACTERISTICS AND VIBRATION CHARACTERISTICS OF TEMPORARY SUPPORT EQUIPMENT IN FULLY MECHANIZED MINING TUNNEL - LU JinNan; XIE Miao; MAO Jun (Jixie qiangdu)
Advanced support equipment is mainly composed of two sets of frames which can be passed by each other,and it is belong to fully mechanized mining roadway roof temporary support equipment. In order to improve the stability and avoid the resonance of the advanced support equipment,based on the analysis of the working principle of the advanced support equipment,proposed the mechanical model of the support system,establish the dynamic mathematical model and the state space model of the advanced support equipment using the Lagrange method and the generalized space coordinate system. Using the Routh Hurwitz criterion as its dynamic stability judgment conditions,refer to the disturbance force mathematical model of commonly used in coal mine,combined with MATLAB and modern control theory,the vibration characteristics of the single support group of the advanced support equipment are simulated,and obtain the system dynamic response. At last,carry out modal analysis using experimental prototype and vibration testing system of advanced support equipment. The research results show that the frequency range of the easy to occur resonance is about 42. 353-42. 994 Hz.